Sleep disturbance, associated symptoms, and quality of life in adults living with HIV in Jakarta, Indonesia. Issue 1 (2nd January 2021) - Pujasari, Hening; Levy, Judith; Culbert, Gabriel; Steffen, Alana; Carley, David; Kapella, Mary
ABSTRACT: Adverse symptom experiences, including sleep disturbances, are important negative predictors of quality of life (QoL), but few studies conducted in low-income countries have examined the impact of poor sleep and its associated symptoms on QoL among people living with HIV (PLWH). To this end, 200 PLWH who were receiving treatment with antiretroviral therapy (ART) were recruited through a community nongovernment organization in Jakarta, Indonesia. Validated instruments measured QoL, sleep disturbance, fatigue, pain, ART adherence, substance use, drug use severity, and methadone treatment. Descriptive statistics, bivariate correlations, and multivariate linear regression were conducted to identify independent correlates of QoL. Overall, participants perceived their QoL as being good to very good (mean = 105.70, standard deviation = 14.7) and higher among women than men ( p < 0.05). After adjusting for sex, education, drug-use severity, and ART adherence, QoL was negatively associated with fatigue, insomnia, and pharmacological treatment with methadone. Along with other known symptoms of HIV, sleep problems and their complications are important to clinically address and research more fully to assure satisfying QoL among PLWH.